Impression Management Tactics as a psychological booster for the communication of IT employees – SMART PLS Approach - Vijayabanu, C. (2019)
Impression management (IM) is a technique or tactic followed by employees to form favorable perceptions. The current study analyzed the relationship of various facets (Deception, Defensive, Exemplification, Ingratiation, Model behavior, and Self-promotion) of impression management and its effect on global assignment, work-life balance, and career growth. Furthermore, the current study also analyzed the impact of IM on the psychological behavior of IT employees and conceptualized a model using SmartPLS (Partial Least Squares) approach. Questionnaires were distributed to 225 employees (36% female) in a Private Software Company in Chennai, India. Results indicate that the IM facets contribute 51.2% in predicting the individual psychological factor composed of global assignment, work-life balance, and career growth.